Pengaruh Pandemi, Restrukturisasi, Dan Pinjaman Agunan Terhadap Kepuasan Pengusaha Mikro PT Pegadaian Cabang Pringgan - Fernando Fernando; Warnita Halawa; Rizky Wulandini; Deni Faisal Mirza; Nur M Ridha Tarigan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study was conducted at Pt Pegadaian Pringgan Branch. The purpose of this study was to examine the effect of the pandemic, restructuring and collateral loans on the satisfaction of microentrepreneurs at PT. Pringgan Branch Pawnshop. The approach in this study is a quantitative approach. This type of research is a quantitative descriptive research. The population was 250 personnel employees and the sample was 71 personnel employees. Sampling technique Using Simple Random Samplin. Data collection using questionnaires, interviews and documentation. Data analysis techniques using multiple linear regression anÃ¡lisis. The conclusion of this study states that the pandemic has a significant effect on the satisfaction of micro entrepreneurs fostered by PT Pegadaian where the Sig value is < 0.05. Restructuring significantly affect the satisfaction of micro entrepreneurs fostered by PT Pegadaian where the value of GIS <0.05. Collateral loans have a significant effect on the satisfaction of micro entrepreneurs fostered by PT Pegadaian where the Sig value is < 0.05. Simultaneously with the pandemic, restructuring and collateral loans had a significant effect on the satisfaction of microentrepreneurs fostered by PT Pegadaian, where the Sig value was < 0.05. Adjusted value of RSquare is 0.733 or 73.30%, meaning that the research variables contribute greatly in explaining the satisfaction of micro entrepreneurs fostered by Pt Pegadaian at 73.30% while the remaining 26.70% is influenced by other factors outside this study. Keywords: Collateral loans, Pandemic, Restructuring, Satisfaction of Microentrepreneurs.